PEMBUATAN APLIKASI PRAKTIS DESAIN BLOK ACAK LENGKAP MENGGUNAKAN BAHASA PEMROGRAMAN LAZARUS - Budhi Handoko; Yeny Krista Franty; Gumgum Darmawan (Universitas Jenderal Soedirman, 2017)
Completely Randomized Block Design is one type of design experiments in Statistics which is used to conduct experiment involving treatments and blocks. Blocking is used to make experimental unit become homogen in each blok. Analysis to the reults of the experiment using the design usually perform using licensed software such as SPSS or Minitab. In order to use those softwares, we have to buy the license. In addition, if use them, we have to arrange the data into column form which require knowledge about orthogonality principle. This research will develop an application to analyze the experimental data easily, because the input in the form of table that suitable with experimental data format. In this research we used Lazarus Visual Programming which is one of open source software. The result of this research is a practical application that can be used to analyze experimental result produced using completely randomized block design which is bery easy to use. Experimental data from table of experimental result can be directly copied into the cells of the program thus data entry can be fastened. This program is an executable file (*.exe) so it is not necessary to be installed and the size of file is small enough which is 19 megabyte.